EVALUATING NEONATAL OUTCOMES IN PREGNANCIES COMPLICATED BY MATERNAL TYPE 2 DIABETES - ARA , F; QURESHI , QUA; MANSOOR , M; SHOAIB , M; BIBI , S; JAVED , SQ (Biological and Clinical Sciences Research Journal, 2024)
Maternal type 2 diabetes during pregnancy presents complex challenges that necessitate careful management due to its multifaceted impacts on both the mother and the neonate. Objective: The basic aim of the study is to find the neonatal outcomes in pregnancies complicated by maternal type II diabetes. Methods: This retrospective observational study was conducted at Sandeman Provincial Hospital from April 2022 to March 2023. Data were collected from 80 participants. Data were collected retrospectively from medical records, focusing on maternal, fetal, and neonatal parameters. Maternal records included demographic details such as age, body mass index (BMI), and parity, as well as clinical information on glycemic control measured by HbA1c levels recorded at various points throughout the pregnancy. Results: Data were collected from 80 patients with type 2 diabetes, with an average maternal age of 32.35 years and an average BMI of 28.5 kg/m². Primiparous women constituted 40% of the sample. The average HbA1c level was 7.5%, with 56.25% of participants achieving good glycemic control (HbA1c ≤ 7%) and 43.75% classified as having poor glycemic control (HbA1c > 7%). The results indicate that the average neonatal birth weight was 3,400 ± 500 grams. Macrosomia was observed in 31.25% of cases, with a significantly higher occurrence in the poor glycemic control group (51.4%) compared to the good glycemic control group (15.6%). Conclusion: It is concluded that poor glycemic control in pregnancies complicated by maternal type 2 diabetes is significantly associated with adverse neonatal outcomes, including macrosomia, neonatal hypoglycemia, congenital anomalies, and higher NICU admission rates.